Hurleytrematoides justinei n. sp. (Digenea: Monorchiidae) from Valentinnis sharpnose puffer, Canthigaster valentini (Bleeker) (Tetraodontiformes: Tetraodontidae) from Heron Island, Queensland, Australia - Mcnamara, Marissa K. A.; Cribb, Thomas H. (Zootaxa, 2009)
A new species, Hurleytrematoides justinei n. sp., is described from Valentinni’s sharpnose puffer, Canthigaster valentini, from Heron Island, Queensland, Australia. It is characterized within the genus by a sinistral genital pore opening anterior to the posterior margin of the ventral sucker, a spiny ejaculatory duct ranging from 34 to 61 µm in length, and vitelline follicles extending from about the anterior margin of the testis to the posterior margin of the ventral sucker. Monorchiids are rare in the tetraodontids. This is the third species reported from the family and the first from the genus Canthigaster.